Simulation of thin-walled double hexagonal aluminium 5754 alloy foam-filled section subjected to direct and oblique loading - Abdulqadir S.; Alaseel B.; Ansari M.N.M. (Elsevier Ltd, 2023)
Crashworthiness; Crushing; Decision making; Dynamic loads; Loading; Thin walled structures; Tubes (components); Aluminium foam; Direct loading; Double tube; Dynamic loadings; Foam filled; Hexagonal; Hexagonal tubes; Oblique loading; Thin walled tubes; Thin-walled; Energy absorption